The dialogic relationship between the curriculum and the pedagogical model - Cruz Picón, Pablo Emilio (2021)
Education and its current role in society is a subject in which heterogeneous perceptions and possibilities converge; In particular, it has been approached from multiple perspectives to inquire how the educational curriculum responds to the increasingly permeable and complex social and cultural needs. Therefore, the objective of the article resides in reflecting on the educational and sociocultural connotations of the dialogic relationship of the curriculum with the pedagogical model. For this purpose, in the reflective exercise was contextualized from a qualitative approach, resorting to a type of exploratory-descriptive research that, based on the analysis of the documentary record, specified the state of the art of the curriculum notions and pedagogical model, as well as the typologies and theories that They support it, since its traceability places the methodological intentionality. Then, the significance of the variables analyzed was related to educational functionality. Within this methodological space, the topics to be examined in the writing had a direct correlation with the theoretical-practical interaction between the curriculum and the pedagogical model. Thus, it was concluded that the processes of teaching for learning are specified in the curriculum, but are based on the pedagogical model. In addition, the two educational elements are associated with the society and the culture that the formation of citizenship projects.